2020
DOI: 10.1021/acs.langmuir.0c02243
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Mediated Forces between Ellipsoidal Nanoparticles Adsorbed at Liquid–Vapor Interfaces

Abstract: Classical capillary theory predicts that a non-neutrally wetting ellipsoidal particle adsorbed at a liquid–vapor interface will deform the interface. The deformation gives rise to anisotropic capillary forces of a quadrupolar nature that induce strong directionality in the particle interactions. Here, we investigate the interactions between nanoparticles with characteristic lengths of 1–5 nm. We show that the near-field interactions are dominated by solvent-mediated forces, which arise from the fluid packing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Similarly, we observed that the grand potential of a fluid in a slit pore is a non-convex function of the distance between the parallel plates at constant chemical potential and temperature [3]. Also, the Helmholtz energy of solid colloids in solution is non-convex as a function of the controlled distance between the colloids, keeping the temperature, volume, and the number of particles constant [18]. Both cases can be explained by a disjoining pressure (also known as the solvation pressure) [19], which is the excess normal pressure relative to the bulk pressure due to the packing of fluid particles between the solids.…”
Section: Introductionmentioning
confidence: 60%
“…Similarly, we observed that the grand potential of a fluid in a slit pore is a non-convex function of the distance between the parallel plates at constant chemical potential and temperature [3]. Also, the Helmholtz energy of solid colloids in solution is non-convex as a function of the controlled distance between the colloids, keeping the temperature, volume, and the number of particles constant [18]. Both cases can be explained by a disjoining pressure (also known as the solvation pressure) [19], which is the excess normal pressure relative to the bulk pressure due to the packing of fluid particles between the solids.…”
Section: Introductionmentioning
confidence: 60%
“… 3 Also, the Helmholtz energy of solid colloids in solution is non-convex as a function of the controlled distance between the colloids, keeping the temperature, volume, and the number of particles constant. 18 Both cases can be explained by a disjoining pressure (also known as the solvation pressure), 19 which is the excess normal pressure relative to the bulk pressure due to the packing of fluid particles between the solids. The observations mentioned all stem from size effects.…”
Section: Introductionmentioning
confidence: 99%
“…The thermodynamic state of a fluid in confinement is important for the understanding of adsorption to walls, chemical reactions, film formation and transport in porous media [ 1 , 2 , 3 , 4 , 5 , 6 ]. The molecular structuring at the walls and the forces between particles and walls are central.…”
Section: Introductionmentioning
confidence: 99%
“…Confinement is considered to be important, for instance, in the context of CO separation and sequestration by metal-organic frameworks [ 2 ] or for adsorption in zeolites [ 3 ]. The disjoining pressure is of interest when studying aggregation of colloidal particles, suspended or adsorbed [ 4 , 5 , 6 ]. It is likely to be important also for film flow on the macroscale [ 8 ].…”
Section: Introductionmentioning
confidence: 99%